Two new species of the Afrotropical genus Ptilothyris Walsingham (Lepidoptera: Lecithoceridae, Torodorinae) from the Ivory Coast - Elliott, Imogen R. (Zootaxa, 2025)
Two new species of the genus Ptilothyris Walsingham, 1897 are described from the Ivory Coast (P. pollex sp. nov. and P. taiensis sp. nov.), serving as the first record of Ptilothyris in the country and the westernmost in the Afrotropical region. Adults and genitalia are illustrated for each new species.